Estimates of Quaternary Philippine coastlines, land bridges, submerged river systems and migration routes: A GRASS GIS approach - Robles, Emil Charles (Hukay; Vol 18, 2013)
This study uses Geographic Information Systems to reconstruct Philippine palaeocoastlines and palaeoriver channels for different sea levels during the Quaternary Period using topographic and bathymetric data. Island connections and land area calculations show drastic changes in land-sea configurations with respect to changes in the levels of the oceans. Least cost path analysis also shows the effects of sea levels in terms of the possible migration routes for different islands in the Philippines. Results are shown as maps that can serve as guides in the study of Philippine palaeohistory and biogeography.